Aplikasi Scanner Berbasis Android Untuk Menampilkan Data Beserta ID Mahasiswa Menggunakan QR CODE - Joko Purnomo; Khurotul Nuraini; Putri Intan Mogot; Taufik Hidayat (Shofanah Media Berkah, 2023)
On this occasion,I will design. and develop a QR code for student identification card (KTM) detection application. This application makes it easy for campus security to verify student identities quickly and accurately. This development utilizes the Rational Unifed Process (RUP) method with the stages of needs analysis.The design,implementation,and testing in this study demonstrate application built is able to accurately recognize the QR code on students' KTM and provide fast identity verification